Evaluating Outcomes of Alternative Dosing Strategies for Cefepime: A Qualitative Systematic Review. (March 2015) - Burgess, Sarah V.; Mabasa, Vincent H.; Chow, Ivy; Ensom, Mary H. H.
Objective: To perform a qualitative systematic review of the evidence comparing traditional with prolonged intermittent or continuous infusions of cefepime based on clinical and pharmacodynamic outcomes.Data Sources: PubMed (1946 to October 2014), EMBASE (1980 to October 2014), CENTRAL, Cochrane Database of Systematic Reviews, Web of Science, and International Pharmaceutical Abstracts (1970 to October 2014) were searched using the terms cefepime, pharmacokinetics, pharmacodynamics, drug administration, intravenous infusions, intravenous drug administration, continuous infusion, extended infusion, and intermittent therapy . Reference lists from relevant materials were reviewed.Study Selection and Data Extraction: Articles evaluating administration regimens of cefepime, one of which included the traditional, manufacturer-recommended 0.5-hour infusion and the other a prolonged or continuous infusion were included. Prespecified clinical outcomes of interest included all-cause mortality, length of hospital stay, clinical cure, and adverse events. The primary pharmacodynamic outcome was percentage time of unbound drug concentration remaining above the minimum inhibitory concentration.Data Synthesis: In all, 18 studies were included; 6 studies assessed clinical outcomes, and 12 assessed pharmacodynamic outcomes. Prolonged or continuous infusions of cefepime achieved the pharmacodynamic targets more often than traditional infusions. The association of improved clinical outcomes with prolonged or continuous infusions is unclear. All-cause mortality was significantly decreased with the use of a prolonged cefepime infusion in a retrospective study. Two prospective, randomized studies demonstrated no statistically significant difference in mortality between prolonged and intermittent infusions.Conclusions: The available literature on prolonged and continuous infusions of cefepime demonstrated an improved achievement of pharmacodynamic targets; however, the effect on clinical outcomes is inconclusive. Well-designed prospective studies are required to determine optimal dosing and administration strategies.